2020
DOI: 10.1029/2019ja027675
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone‐Induced Gravity Wave Perturbations in the Upper Atmosphere: GITM‐R Simulations

Abstract: The tropical cyclone (TC)‐induced concentric gravity waves (CGWs) are capable of propagating upward from convective sources in the troposphere to the upper atmosphere and creating concentric traveling ionospheric disturbances (CTIDs). To examine the CGWs propagation, we implement tropical cyclone‐induced CGWs into the lower boundary of global ionosphere‐thermosphere model with local‐grid refinement (GITM‐R) and simulate the influence of CGWs on the ionosphere and thermosphere. GITM‐R is a three‐dimensional non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
5
15
0
Order By: Relevance
“…Since the background values of electron density were smaller at 100–250 km altitudes, the percentage of electron density disturbances was significant in this altitude range, which was comparable to the simulation results of Zhao et al. (2020). Moreover, some small‐amplitude wave‐like disturbances during 6:30 and 8:00 UT were more salient in Figure 11b.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Since the background values of electron density were smaller at 100–250 km altitudes, the percentage of electron density disturbances was significant in this altitude range, which was comparable to the simulation results of Zhao et al. (2020). Moreover, some small‐amplitude wave‐like disturbances during 6:30 and 8:00 UT were more salient in Figure 11b.…”
Section: Resultssupporting
confidence: 89%
“…The horizontal propagation parameters of the CTIDs obtained using GNSS-TEC in this study are comparable to those in previous studies. Zhao et al (2020) obtained a similar time-distance-disturbance relationship (Figure 6) in the simulation of tropical cyclone-induced CGWs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…They found that the TIDs are most likely induced by secondary gravity waves from local horizontal body forces created by the dissipation of primary gravity waves from deep convection. These findings have also been confirmed by other studies (Liu et al, 2021;Maurya et al, 2019;Miyoshi et al, 2018;Snively & Pasko, 2008;Vadas & Becker, 2018;Zhao et al, 2020). To date, the effects of convective activity on the ionosphere have various explanations.…”
supporting
confidence: 83%
“…It explicitly solves for the densities, velocities, and temperatures of neutrals, ions, and electrons in the spherical coordinate system. Unlike most GCMs used in the community, GITM relaxes the hydrostatic assumption which allows propagations of acoustic waves (Deng et al, 2008(Deng et al, , 2011Lin et al, 2017;Zhao et al, 2020;Zhu et al, 2017) and gives a more accurate description of high-frequency gravity wave propagation (Deng & Ridley, 2014). More details about GITM can be found in Ridley et al (2006).…”
Section: Global Ionosphere and Thermosphere Modelmentioning
confidence: 99%